PENGARUH LATIHAN BENCH DIP TERHADAP KEKUATAN OTOT LENGAN DAN BAHU PADA TIM BOLAVOLI PUTRA SMA KUSUMA PEKANBARU - Joel Rejeki Pasaribu; Slamet Slamet; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The purpose of this study to know the effect of bench dip exercise toward the strength of arm and shoulder muscles at male volleyball team of SMA Kusuma Pekanbaru. In this study the researchers took the population of male volleyball team SMA Kusuma Pekanbaru, amounting to 8 people. The sample in this research used total sampling technique which is the full sampel of total population. The design of this study using one group then this research approach to wear one gruop pretest-posttest design. The instrument used in this research to measure the strength of the arm and shoulder muscles with expanding dynamometer. After that, the data is processed with statistical, normality test with lilifors test at significance level α (0,05). The hypothesis is the effect of bench dip exercise toward the arm and shoulder muscle strength. Based on the analysis of statistical data, produces data pretest Lcount is 0.235, data posttest Lcount is 0.277 and Ltabel is 0.285, it means Lcount < Ltabel. Then the data is normally distributed. Based on t test analysis, it produces Tcount is 23.88 and Ttable is 1.895, it means Tcount > Ttable. Thus, there is an Effect of bench dip Exercise toward the Strength of Arm And Shoulder muscle at Male Volleyball Team of SMA Kusuma Pekanbaru.Keywords: Bench Dip, the strength of arm and shoulder muscle